Reduced Vitellogenesis and Female Fertility in Gper Knockout Zebrafish - Wu, Xin-Jun; Williams, Marcus Jermaul; Kew, Kimberly Ann; Converse, Aubrey; Thomas, Peter; Zhu, Yong (Frontiers in Endocrinology, 2021)
The role G-protein coupled estrogen receptor (GPER) plays in vertebrate reproduction remains controversial. To investigate GPER’s reproductive role, we generated a gper zebrafish mutant line (gper-/-) using TALENs. Gper mutant females exhibited reduced fertility with a 40.85% decrease in embryo production which was associated with a significant decrease in the number of Stage V (730-750 μm) ovulated oocytes. Corresponding, the number of early vitellogenic follicles (Stage III, 400-450 µm) in gper-/- ovaries was greater than that in wildtypes (wt), suggesting that subsequent follicle development was retarded in the gper-/- fish. Moreover, plasma vitellogenin levels were decreased in gper-/- females and epidermal growth factor receptor (Egfr) expression was lower in Stage III vitellogenic oocytes than in wt counterparts. However, hepatic nuclear estrogen receptor levels were not altered and estrogen levels were elevated in ovarian follicles. These results suggest that Gper is involved in the control of ovarian follicle development via regulation of vitellogenesis and Egfr expression in zebrafish.